Corporate Governance and Development : An Update - Claessens, Stijn; Yurtoglu, Burcin (International Finance Corporation, Washington, DC, 2017)
What do we know about the links between economic development and corporate governance in emerging markets? Stijn Claessens and Burcin Yurtoglu have sifted through scores of academic studies on various countries, sectors, and business organizations - from state-owned enterprises to publicly listed companies - to determine how corporate governance can influence economic development and well being, and what is needed to promote good practices. The Focus 10 draws on new evidence that has become available since Focus 1: Corporate Governance and Development was published in 2003. While the paper reviews research literature, it is written to be accessible to the nonacademic audience: board members, investors, government regulators, development professionals, and other CG practitioners. Research findings sited in the Focus include: 1) improved corporate governance practices increase firm share prices; 2) operational performance is higher in better corporate governance countries; 3) well governed companies have less volatile stock prices in times of crisis; 4) companies with boards composed of a higher fraction of outsider or independent directors usually have a higher market valuation; 5) improvements in corporate governance quality lead to higher GDP growth, productivity growth, and the increased ratio of investment to GDP; 6) when a country's overall corporate governance and property rights systems are weak, voluntary and market corporate governance mechanisms have limited effectiveness; 7) large, more concentrated ownership can be beneficial, unless there is a disparity of control and cash flow rights; 8) the quality of shareholder protection positively correlates with the development of countries' capital markets; and 9) better corporate governance leads to a better developed financial system. The paper concludes by identifying several main policy and research issues that require further study. For example, more research is needed on family-owned, state-owned or controlled firms that predominate in many sectors and economies. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.